Urinalysis Profile of Dengue Viral Infection Patients in Dr. Soetomo General Academic Hospital, Surabaya, from 2019-2021 - Rahardjo, Albertus Reiner; Wardhani, Puspa (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2023)
Highlights:1. Dengue viral infection patients were mostly male and aged 17-45 years old.2. Dengue viral infection patients mostly have normal urinalysis results.3. Some dengue viral infection patients can have elevated protein, blood, bilirubin, urobilinogen, leukocytes esterase, and ketones in the urine. AbstractIntroduction: Dengue viral infection is still a burden in Indonesia. It often causes some kidney complications such as acute renal failure, proteinuria, hematuria, and glomerulonephritis. Urinalysis is an easy and useful examination of kidney complications. This study aimed to discover the most common profile of urinalysis in dengue viral infection.  Methods: This study used a cross-sectional method with medical records data of patients with dengue viral infection in Dr. Soetomo General Academic Hospital, Surabaya, in the 2019-2021 period. Purposive sampling techniques were used with inclusion and exclusion criteria. Data such as age, gender, dengue viral infection severity level, and dipstick urinalysis results were taken and analyzed using descriptive analysis in SPSS Statistics 25.Results: A total of 276 patients were included. The sample was dominated by male patients (52.9%) and patients aged 17-45 years old (40.2%). Most patients suffered from dengue hemorrhagic fever/DHF (54.3%) followed by dengue fever (45.7%). DHF was categorized into grade I (28.3%), grade II (13.4%), grade III (8.3%), and grade IV (4.3%). Most urinalysis results were normal and followed by increased results of protein, blood/hemoglobin, bilirubin, urobilinogen, leukocytes esterase, and ketones in some patients.Conclusion: Dengue viral infection was more common in male patients and 17-45 years old patients. The most common diagnosis was DHF. Urinalysis results in dengue viral infection were mostly normal. Follow-up research is needed to find the relation between the elevated urinalysis results and the severity of dengue viral infection.